Improvements on Clinical Status of Adolescents With Anorexia Nervosa in Inpatient and Day Hospital Treatment: A Retrospective Pilot Study - Zanna, Valeria; Cinelli, Giulia; Criscuolo, Michela; Caramadre, Anna Maria; Castiglioni, Maria Chiara; Chianello, Ilenia; Marchili, Maria Rosaria; Casamento Tumeo, Chiara; Guolo, Stefano; Tozzi, Alberto Eugenio; Vicari, Stefano (Frontiers in Psychiatry, 2021)
Introduction: Medical and psychiatric complications and treatment compliance are important considerations in determining the treatment program for patients with severe AN. Clinical practice guidelines agree that an outpatient program is the first choice for the treatment of most Eating Disorders, but vary in supporting these programs for Anorexia Nervosa (AN). However, inpatient care is known to be costly and the risk of relapse and readmission are high. This pilot study aimed to describe the first data on an Italian partial hospitalization care program for AN adolescents (High-Level Care Treatment; HLCT), evaluating its impact on patients’ clinical status, average hospitalization time and the hospital costs compared to Inpatient treatment (IP). Methods: For this retrospective pilot study we have selected a group of 34 females with AN aged 11-18 years, divided between those who followed inpatient treatment and those who received HLCT treatment; they were matched for age and severity. We investigated the differences in treatment and outcomes between the two groups in terms of heart rate, length of treatment, weight gain, psychological characteristics and hospital costs. Statistics for non-parametric distributions were used to compare the two groups. Results: No differences between the two groups were found at admission. At discharge, patients in the HLCT group presented a lower number of in hospital treatment days, a higher increase of weight and a significant improvement in outcomes compared to the inpatient group. No significant differences were found in heart rate and hospital costs. Conclusions: This study represents a first comparison between inpatient care and the HLCT treatment program, which suggests that day hospital treatment could represent a meeting point between inpatient and outpatient treatment, combining the merits of both forms of treatment. Further studies are needed in order to better investigate the different treatment programs for severe AN in adolescence.